PERJANJIAN PEMBORONGAN PEMBANGUNAN SEKOLAH (STUDI DI KABUPATEN LOMBOK BARAT) - Dedik Purnomo Aji; H. Zaenal Arifin Dilaga (Private Law, 2021)
This work aims are to know and to explain implementation of charter school development agreement and also to know the default settlement mechanism of the agreement between West Lombok Regency Local Government and CV. Cahaya Lestari. This research is normative legal research. The school development charter agreement implemented in written form in direct appointment by the Education and Culture Office of West Lombok Regency to the CV. Cahaya Lestari, however the default settlement mechanism in this agreement between parties are by discussion to accelerate the settlement process thus CV. Cahaya Lestari could continue their project according to the agreed due date.